2011
DOI: 10.1007/s00737-011-0230-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy and cognitive functions in healthy postmenopausal women: a randomized trial

Abstract: This study aimed to evaluate the effect of estrogen replacement therapy on verbal cognitive performance of middle-aged postmenopausal women. Middle-aged (40 to 59 years) hysterectomized, oligosymptomatic women receiving 0.625 mg/day of conjugated equine estrogens (N = 27) or placebo (N = 32) in a double-blind parallel group design were compared according to their performance on a verbal memory battery before and after six 28-day cycles of treatment. Both groups had similar age and educational level. The estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…In contrast to the variable outcomes associated with combined hormone treatments, investigations of unopposed estradiol have largely found positive or neutral effects on verbal cognition, although results from studies using conjugated equine estrogens (CEE) have been less conclusive (Dumas et al, 2010; Espeland et al, 2013; Gleason et al, 2006; Gorenstein et al, 2011; Maki, 2012; Maki and Sundermann, 2009; Sherwin, 2012; Sherwin and Grigorova, 2011; Wroolie et al, 2011). We expected that short-term estradiol administration would positively impact verbal cognition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the variable outcomes associated with combined hormone treatments, investigations of unopposed estradiol have largely found positive or neutral effects on verbal cognition, although results from studies using conjugated equine estrogens (CEE) have been less conclusive (Dumas et al, 2010; Espeland et al, 2013; Gleason et al, 2006; Gorenstein et al, 2011; Maki, 2012; Maki and Sundermann, 2009; Sherwin, 2012; Sherwin and Grigorova, 2011; Wroolie et al, 2011). We expected that short-term estradiol administration would positively impact verbal cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral animal and human subject studies show that the effects of estrogen on cognition are task, time, and dose dependent. That estrogen has been shown to significantly improve performance on PFC dependent cognitive tasks such as the N‐back task [Keenan et al, ], Stroop task [Krug et al, ], and digit‐span forward task [Gorenstein et al, ] in human subjects and the delayed response task in rodents [Inagaki et al, ] and non‐human primates [Rapp et al, ], suggests estrogen may play a significant role in mediating executive domains such as working memory and sustained attention. The cognitive load required by a particular task also appears to play a role in both the extent to which ET enhances cognitive function and brain activation with more obvious effects of estrogen at higher cognitive loads [Dumas et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, Smith and colleagues reported that early initiation of HT in menopausal women is associated with increased hippocampal and posterior cingulate cholinergic activity (Smith et al, 2011). Similarly, Gorenstein et al evaluated the effect of estrogen replacement therapy on verbal cognitive performance of middleaged postmenopausal women and reported better performance of the estrogen group on digit span-forward and on the recall of the easy stimuli on the verbal-paired associates tests despite the magnitude of benefits is moderate (Gorenstein et al, 2011). …”
Section: Healthy Cell Bias Of Estrogen Action: Consolidation Of Cmentioning
confidence: 99%